Peran Humas Dalam Penyampaian Edukasi Ham Di Sekolah Pada Kantor Wilayah Kementerian Ham Sumatra Selatan - Bayhaqi, Muhammad Reyvalza; Saputra , Ade Akhmad (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The role of public relations in the delivery of Human Rights (HAM) education in schools is an important part in building legal awareness and human rights culture in students from an early age. The Regional Office of the Ministry of Human Rights of South Sumatra has a strategic responsibility in carrying out the dissemination of human rights values through socialization, counseling, and public communication activities to the educational environment. This study aims to analyze the role of public relations of the Regional Office of the Ministry of Human Rights of South Sumatra in delivering human rights education in schools and to find out the communication strategies used in building students' understanding of the importance of respect and protection of human rights. The research method used was qualitative descriptive with data collection techniques through interviews, observations, and documentation. The results of the study show that public relations plays a role as an information facilitator, communication mediator, and institutional image shaping through a persuasive, educative, and cooperative approach with schools. The human rights education program carried out is able to increase students' understanding of human values, tolerance, and legal awareness in the school environment. In addition, the use of social media and direct communication also supports the effectiveness of public information delivery. This study concludes that the role of public relations is very important in supporting the creation of schools that are aware of human rights and have a legal culture in South Sumatra.